Cognitive biology dealing with information from bacteria to minds - Auletta, Gennaro, 1957- (Oxford : Oxford University Press, 2011)
Providing a new conceptual scaffold for further research in biology and cognition, this text introduces the new field of cognitive biology, treating developing organisms as information processors which use cognition to control and modify their environments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Biology -- Philosophy; Cognitive science; Evolution (Biology)